Indigenous Knowledge on Use of Local Fodder Trees in Mid Hills of West Nepal - Panthi, Mohan P. (Tribhuvan University Journal, 2013)
Fodder shortage (quality as well as quantity) has been found through outmid hills of Nepal. The tree fodder is particularly important as a green, nitrogen supplement to poor quality crop residues during the dry season when feeds are scarce. The nutritional values of fodders differ according to species and season therefore farmers prefer different species for different seasons to feed their livestock. The choice or preference of fodder species by farmers reflects their traditional knowledge on nutritional values, palatability, cultivation easiness and seasonal variability of tree fodder in local environment. The paper highlights an indigenous knowledge system that relates to the quality of tree fodder used by farmers in mid hills of Nepal. In total 69 plant species have been recorded as tree fodder and out of them ten best tree fodders have been listed on the basis of preferences and priority by farmers. Information was gathered through a semi structured open questionnaire by interviewing 85 respondents of different age groups of Arghakhanchi district. Though Focus species was the most abundant among tree fodder, Grewia optiva (locally known as 'phorso') was found the most preferable tree fodder species in the study area.